Speeches on labour - Bandaranaike, S. W. R. D. (Solomon West Ridgeway Dias), 1899-1959 (Labour Secretariat, 1976)
Speeches delivered in the legislature during the period 1931-1958, by a former prime minister of Sri Lanka.